Promoting Foundation Reading Skills With At-Risk Students - Sucena, Ana; Silva, Ana Filipa; Marques, Cátia (Frontiers in Psychology, 2021)
This paper presents an early reading intervention program, the PPCL (Programa de Promoção das Competências Leitoras – Promoting Reading Skills Program). PPCL focuses on the promotion of reading foundation abilities – letter-sound, phonemic awareness, decoding and spelling – with at-risk first graders. This study assessed the impact of PPCL on the reading foundation abilities with 311 first graders (173 boys and 138 girls), divided between intervention and comparative group (respectively, 206 and 105 first graders). Results were analysed with an inter- (intervention and comparative group) and intra- (pre-and post-test) group design. A mixed two-way Manova indicated the presence of statistically significant differences between the two assessment moments, with the intervention group presenting higher values than the comparative group in all abilities at the post-test and also above the cutoff score in all variables, which indicates that once at-risk students eventually concluded the school year with satisfactory levels of reading skills. Instead, the comparative group scored below the cutoff score in all variables. The magnitude of the effect on the intervention group was higher than that observed for the comparative group. Reading promotion with PPCL significantly improved at-risk students reading skills. In future studies, it is the authors’ intention to follow-up reading and writing participants skills.